Sugar Sweetened Beverage Consumption among Adults with Gout or Type 2 Diabetes. - Rinki Murphy (PLoS ONE, 2015)
Current guidelines for the management of type 2 diabetes and gout recommend that people with these conditions limit their sugar sweetened beverage (SSB) intake. We examined self-reported SSB intake among New Zealand adults with gout or type 2 diabetes, including those on hemodialysis.1023 adults with gout and 580 adults (including 206 receiving hemodialysis) with type 2 diabetes, participated in this study of between 2009 and 2012. Participants completed an interviewer-administered SSB intake question "how many sugar sweetened drinks (including fruit juice), but not including diet drinks, do you normally drink per day?" SSB consumption was recorded as a circled number 0, 1, 2, 3, 4, 5, or >5, cans or large glasses (300 mL) per day.Consuming one or more SSB per day was reported by 64% (622/1023) of subjects with gout, 49% (176/374) with type 2 diabetes without dialysis, and 47% (96/206) with diabetes on dialysis. Consuming four or more SSBs per day was reported by 18% (179/1023), 9% (31/374) and 9% (18/206), respectively. Such high consumers of SSB were characterized after multivariable analysis to be more likely to be male (adjusted odds ratio (OR) 1.8; 95% confidence interval 1.1-2.9), younger in age (40 vs 65 years: 1.6; 1.1-2.3), current smoker (5.2; 2.7-10.1), obese (BMI 41 vs 26 kg/m(2): 1.4; 1-1.9), and report Māori (1.8; 1.2-2.8) or Pacific (1.6; 1.1-2.5) ancestry, compared to Caucasian. People with gout were more likely to report heavy SSB intake compared to people with diabetes (OR 2.4, 95% CI 1.5-3.9). Heavy SSB consumption reported by people with diabetes was similar if they did or did not require dialysis.A high proportion of patients with gout and type 2 diabetes, including those on haemodialysis, are not responding to health messages to abstain from SSB consumption.